Avaliação da orientação médica sobre os efeitos colaterais de benzodiazepínicos - Auchewski, Luciana (2004)
OBJECTIVES: Benzodiazepines are among the most prescribed drugs indicated as anxiolytics, hypnotics, myorrelaxants or antiepileptics. Their main side effects are: reduced psychomotor activities, interaction to other drugs, like alcohol, and the development of dependence. In the present study it was evaluated the quality of the medical directions given to patients about those side effects. METHODS: One hundred and twenty patients (39 men and 81 women), mean age of 48 years old, who visited pharmacies in Curitiba to buy prescribed benzodiazepines, were interviewed by an open or directive questionnaire designed to obtain the medical directions about benzodiazepines side effects. RESULTS: Directions about the three main benzodiazepines side effects were observed only in 13% of the patients, 27% had received at least two and 40% only one, while 19% reported no directions. It suggested that the medical orientation was precarious and its quality was not influenced by the patients' educational level, the kind of medical attendance or the specialty of the physician. The main orientation cited was ''don't drink'' (85%), followed by ''don't drive or operate machines'' (46%), while few orientations about the risk to develop dependence on benzodiazepines was observed (31%). CONCLUSION: This suggests that physicians were worried about the alcohol interaction risk, which can be dangerous for the patients. The high number of patients using benzodiazepines continuously for more than one year (61%), the unsuccessfully attempt to stop using BZD (94%) and the poor information about the duration of the treatment (22%) were all related to the low medical worry about dependence on benzodiazepines.